Pain Management - Practices, Novel Therapies and Bioactives 2021
DOI: 10.5772/intechopen.93265
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Potential of Monoterpenes from Citrus Essential Oils

Abstract: Chronic pain is a noteworthy health issue with immense impact on global healthcare systems. Although this issue has not come into the limelight as other noncommunicable diseases, it should be highlighted that modern medicine still has no efficient treatment to curb chronic pain. In this aspect, essential oils have been used for the prevention of several disease conditions including pain management. These odorous products, obtained from botanically defined raw material, have a variable and complex composition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…This could be attributed to the presence of D-Limonene as shown in studies of different models of nociception without opioid receptor stimulation (42). In addition, a study has revealed that monoterpenes are the key holders of analgesic potential in Citrus essential oils, especially D-limonene and linalool (43). This explains why there was no significant reduction in inflammation with lemon oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the presence of D-Limonene as shown in studies of different models of nociception without opioid receptor stimulation (42). In addition, a study has revealed that monoterpenes are the key holders of analgesic potential in Citrus essential oils, especially D-limonene and linalool (43). This explains why there was no significant reduction in inflammation with lemon oil.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that the synergistic effects observed with the ginger/lemon and turmeric/lemon oil blends as against lemon alone, are due to the combined reaction mechanisms against rheumatoid arthritis, attributable to an abundance of monoterpenes in lemon oil (17,43), and an abundance of sesquiterpenes in ginger and turmeric oils (9,35).…”
Section: Discussionmentioning
confidence: 99%